2017
DOI: 10.1103/physrevb.95.245303
|View full text |Cite
|
Sign up to set email alerts
|

Current-induced nonuniform enhancement of sheet resistance in Ar+ -irradiated SrTiO3

Abstract: The sheet resistance Rs of Ar + irradiated SrTiO3 in patterns with a length scale of several microns increases significantly below ~40 K in connection with driving currents exceeding a certain threshold. The initial lower Rs is recovered upon warming with accelerated recovery around 70 and 160 K. Scanning SQUID microscopy shows local irreversible changes in the spatial distribution of the current with a length scale of several microns. We attribute the observed non-uniform enhancement of Rs to the attraction o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Below T 105 K, STO undergoes a structural transition from a cubic to a tetragonal phase [41,42]. Current maps of charge flow in LAO/STO reveals a filamentary structure of the pattern which is related to the striped electrostatic potential modulation arising from the tetragonal domains in STO at low temperature [43][44][45][46][47].…”
mentioning
confidence: 99%
“…Below T 105 K, STO undergoes a structural transition from a cubic to a tetragonal phase [41,42]. Current maps of charge flow in LAO/STO reveals a filamentary structure of the pattern which is related to the striped electrostatic potential modulation arising from the tetragonal domains in STO at low temperature [43][44][45][46][47].…”
mentioning
confidence: 99%
“…Similar anomalies have also been observed in the patterned LAO/STO and STO samples with the length scale of several μm. 28,32,33 The anomalies presenting in these references significantly enhance when the sample length decreases to nm scale, the previous works considered that the anomalies could only occur in several u.c. layers LAO/STO samples with length scale of micron.…”
Section: Resultsmentioning
confidence: 99%
“…Roy and Klein et al also found the current-induced nonuniform enhancement of sheet resistance due to the interaction between domain walls and oxygen vacancies in STO. 28 Erlich et al 30 confirmed the channel behavior of conductivity by using the polarized light microscopy technology. Ma et al 31 carried out SEM imaging at low temperature and found that the ferroelectric can be induced within the twin walls in STO beyond the critical electrical field.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“… 8 10 Further, oxygen vacancies tend to accumulate at STO domain walls and act as channels for the movement of oxygen vacancies that can dramatically influence the dielectric environment both with temperature and with electric fields. 11 , 12 This intricate interplay between structural transition and electronic transport has been studied by several groups using different macroscopic and transport probes involving different levels of complexity. The domain walls were found to host interesting properties, such as field-induced ferroelectricity, high mobilities up to low temperature, and enhanced conductivity.…”
Section: Introductionmentioning
confidence: 99%